2013
DOI: 10.1371/journal.pone.0064130
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two 20kDa-Cement Protein (cp20k) Homologues in Amphibalanus amphitrite

Abstract: The barnacle, Amphibalanus amphitrite, is a common marine fouling organism. Understanding the mechanism of barnacle adhesion will be helpful in resolving the fouling problem. Barnacle cement is thought to play a key role in barnacle attachment. Although several adult barnacle cement proteins have been identified in Megabalanus rosa, little is known about their function in barnacle settlement. In this study, two homologous 20k-cement proteins (cp20k) in Amphibalanus amphitrite, named Bamcp20k-1 and Bamcp20k-2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Finally, discrete points of similarity revealed several other pairs including two 105 kDa proteins (Table 1). Other known homologues (AaCP100/AaCP11434 and AaCP20-1/AaCP20-237) were found to verify the similarity matrix.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Finally, discrete points of similarity revealed several other pairs including two 105 kDa proteins (Table 1). Other known homologues (AaCP100/AaCP11434 and AaCP20-1/AaCP20-237) were found to verify the similarity matrix.…”
Section: Resultsmentioning
confidence: 77%
“…Analysis of transcript sequences collected from the basal membranes of barnacles A. amphitrite and T. japonica confirmed cement proteins are produced in tissues contained just above the baseplate343637. Both studies performed on A. amphitrite have revealed two additional cement proteins that share primary structure and amino acid chemistry with existing sequences, suggesting that barnacles produce cement proteins in specialized subfamilies3437. However, transcriptomic studies have revealed few new proteins in addition to those identified more than a decade ago.…”
mentioning
confidence: 99%
“…These proteins self-assemble into crystalline repeats which are bound together by disulfide bond formation, glycosylation, or cation interactions (Winkler and Kaplan, 2000). Barnacles also secrete an adhesive cement which is used to firmly adhere to their substrate however, barnacle cement differs from the other adhesives listed here as the protein composition of barnacle cement contains cysteine repeats (He et al, 2013) rather than a large number of glycine repeats. However, the two-cement process of barnacles (Burden et al, 2012) mimics the two-cement composition of tick cement.…”
Section: Introductionmentioning
confidence: 99%
“…While the patchy material was first observed with the nucleic acid stains, the protein stains suggest the material was mainly proteinaceous and at least some proteins were phosphorylated. Cyprid adhesive and adult glues contain a large fraction of protein (Kamino and Shizuri, 1998;Urushida et al, 2007;He et al, 2013;Gohad et al, 2014). Phosphoprotein was of particular interest as it was found in the cyprid adhesive plaque (Gohad et al, 2014) and is a critical component of other marine adhesives such as mussel (Waite and Qin, 2001;Flammang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%